Minecraft in Education Benefits Learning and Social Engagement - Alawajee, Omar; Delafield-Butt, Jonathan (International journal of game-based learning, 2021)
Empirical evidence suggests game-based learning (GBL) as a potentially engaging form of contemporary learning. With the increase in the use of Minecraft, a sandbox computer game in open-world format, there has been a concurrent rise in the level of interest in investigating the role of Minecraft in social and academic learning. Minecraft is socially interactive, and its cooperative, rather than competitive, open-world gameplay suggests that it could be used for educational purposes. This paper presents a systematic review of all published peer-reviewed research and synthesises the evidence for and against Minecraft's use in education to better understand the applicability of Minecraft in educational and psychological interventions. Forty-two papers were identified. These revealed Minecraft to be beneficial in terms of increased motivation, language development, and academic learning in subjects such as science and history. Minecraft play also supported the development of social skills, including communication, sharing, collaboration, and leadership. Concerns about age-appropriateness, safety, technology use, and learning generalisation were raised, but on balance, the evidence favours an informed and guided employment of Minecraft for improved opportunities for learning and engagement in education.